Development of a simple structure of milifluidic impedance-based sensor for speed measurement - Ghajar, Masoumeh Asghari (2019)
Microfluidic systems for flow sensing have been widely explored, although the processes involved in their fabrication are lithography intensive making the process quite expensive and cumbersome. The aim of this work is to fabricate a device for fluid detection and identification. Therefore the device development consists of channel and geometry parameters optimisation that are modelled by COMSOL, while further development incorporates microcontroller that allows device to read and display result on LCD and excel datasheet. Fabrication of the device does not require a complicated lab-on-chip process so device can easily be implemented.